2020
DOI: 10.1038/s41598-020-66845-6
|View full text |Cite
|
Sign up to set email alerts
|

Robust detection of undifferentiated iPSC among differentiated cells

Abstract: Recent progress in human induced pluripotent stem cells (iPSC) technologies suggest that iPSC application in regenerative medicine is a closer reality. Numerous challenges prevent iPSC application in the development of numerous tissues and for the treatment of various diseases. A key concern in therapeutic applications is the safety of the cell products to be transplanted into patients. Here, we present novel method for detecting residual undifferentiated iPSCs amongst directed differentiated cells of all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…We also demonstrated that the function of ESRG is not required for recapturing pluripotency via somatic cell reprogramming. Finally, the tightly regulated and high expression of ESRG promises to make an excellent marker of undifferentiated human PSCs both in basic research and clinical application [ 20 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the function of ESRG is not required for recapturing pluripotency via somatic cell reprogramming. Finally, the tightly regulated and high expression of ESRG promises to make an excellent marker of undifferentiated human PSCs both in basic research and clinical application [ 20 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the function of ESRG is not required for recapturing pluripotency via somatic cell reprogramming. Finally, the tightly regulated and high expression of ESRG promises to make an excellent marker of undifferentiated PSCs both in basic research and clinical application [20, 38].…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the potential risk of genomic instability and accumulation of oncogenic mutations [ 65 , 79 ], any iPSC therapy must, however, be extensively genetically screened prior to use [ 48 , 50 ] and any undifferentiated cells need to be detected by robust methods [ 80 ].…”
Section: Alternative Sources Of Schwann Cellsmentioning
confidence: 99%